Disturbances of embodiment as core phenomena of depression in clinical practice - Dörr, Otto; Irarrázaval, Leonor (Psychopathology, 2017)
This paper proposes a phenomenological approach to the diagnosis of depression, with the aim of overcoming the broadness and nonspecificity of the concept of major depressive disorder (MDD) in current systems of diagnostic classification of mental disorders. Firstly, we outline the methodological limitations of the current classification systems for the diagnosis of MDD. Secondly, we offer a conceptual differentiation between a “symptomatological” versus a “phenomenological” diagnosis of depression. Thirdly, we propose characteristic “disturbances of embodiment” as the fundamental phenomena of “core depression”, which manifest themselves in 3 dimensions: embodied self, embodied intentionality, and embodied time. A more useful diagnosis of depression may be achieved by describing the phenomena that constitute a core depression, in order to avoid the overdiagnosis of MDD and its negative consequences in clinical practice.